Geochemical evolution of groundwater in an evaporite karst system: Brujuelo area (Jaén, Spain) - Gil-Márquez, José Manuel; Barberá-Fornell, Juan Antonio; Andreo-Navarro, Bartolomé; Mudarra-Martínez, Matías (My University, 2016)
Chemical evolution of groundwater along two main flowpaths was studied in Brujuelo area, an evaporite plateau characterized by the presence of wetlands and drained by hyper-saline springs. Major ions were analyzed, saturation indexes of the main mineral species were computed, and inverse geochemical modeling was performed. Results show a relationship between elevation and water mineralization, indicating that drainage at higher altitude (brackish water) may be associated to gravity-driven flows while lower altitude springs could drain regional groundwater flows (brine water). Modeling results strongly support the hypothesis that most of the selected springs geochemically evolve in a common (S-N) flowpath.
Keywords: Aguas subterráneas - Flujo; Evaporite rocks; Groundwater flowpath; Hyper-saline spring; Geochemical evolution; Inverse modeling